Pedagogical Inputs for Child Development - Dev, Meenu (JOURNAL OF INDIAN EDUCATION, 2016)
Children are natural learners. They construct their own knowledge and actively engage with the world around by exploring, responding, inventing and working things out to frame their own meaning. Modern pedagogy, strongly influenced by Piaget’s cognivitism and social interactionalist theories of Bruner and the social and cultural theories of Vygotsky, has laid a new foundation for pedagogy, where sequential development of individual mental processes such as recognise, recall, analyse, reflect, apply, create, understand and evaluate are scaffolded. Students learn as they internalise the procedures, organisation and structures encountered in social context as to their own schema. They learn to integrate their prior knowledge with new knowledge and also develop their meta-cognition, ability to learn how to learn. The NCERT National Curriculum Framework (NCF 2005), too, emphasises on learner-centred approach to achieve the objectives of the curriculum and child development in all aspects.